2015
DOI: 10.1007/s00467-014-2970-9
|View full text |Cite
|
Sign up to set email alerts
|

Pauci-immune glomerulonephritis in children: A clinicopathologic study of 21 patients

Abstract: Pediatric patients with pauci-immune GN are similar to their adult counterparts in terms of clinical manifestations and histopathologic findings. Among the 21 patients in our study, those with focal GN had the best outcomes while patients with crescentic, mixed or sclerotic GN overwhelmingly had a poor long-term outcome for kidney function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
7
1
Order By: Relevance
“…These results can predict the progression of renal function to ESRD in children with AAV. However, the results of this study are not entirely consistent with previous studies (33)(34)(35)(36)(37), primarily because of the small sample size, which did not meet the requirements of events per variable (EPV). Although the results might not be stable enough, they were reported considering the rare incidence and absent clinical evidences in children.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results can predict the progression of renal function to ESRD in children with AAV. However, the results of this study are not entirely consistent with previous studies (33)(34)(35)(36)(37), primarily because of the small sample size, which did not meet the requirements of events per variable (EPV). Although the results might not be stable enough, they were reported considering the rare incidence and absent clinical evidences in children.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported that baseline eGFR < 60 ml/min/1.73 m 2 , hypertension, baseline Scr, oliguria/anuria, histopathological classification, and renal tubular atrophy are risk factors for poor prognosis in AAV (33)(34)(35)(36)(37)(38)(39)(40)(41). In this study, the univariate analysis showed that baseline eGFR < 60 ml/min/1.73 m 2 , hypertension, glomerular sclerosis >50% of total glomerular count, mesangial cell, and matrix hyperplasia were risk factors for progression to ESRD in AAV children (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Diseases Research, Research on intractable disease, from the Ministry of Health, Labour and Welfare of Japan. Table 4 shows a summary of previous literature in which pediatric rapidly progressive or crescentic glomerulonephritis has been included [7][8][9][10][11][12][13][14][15][16][17][18]. The patient survival rate was extremely high in these reported cases, consistent with the present study.…”
Section: Plos Onesupporting
confidence: 84%
“…Yin et al6 reported only 10 pediatric cases out of 1579 renal biopsy series of 23 years. In different pediatric studies, mean age at presentation has been reported to range from 11 to 12.27 years while the youngest patient was 3 years old 1 , 3 , 4. Overall prognosis of the condition is poor.…”
Section: Discussionmentioning
confidence: 99%
“…Pauci-immune glomerulonephritis (GN) is more common in adults than in children and it is associated with ANCA positivity in 80% of the patients. ANCA positivity also commonly accompanies small vessel vasculitis such as granulomatosis with poliangiitis, microscopic poliarteritis nodosa (PAN), and Churg-Strauss syndrome 1. Pauci-immune GN is one of the usual patterns of renal involvement in these vasculitic syndromes.…”
Section: Introductionmentioning
confidence: 99%